Successful repair of Aortic Rupture in a patient with bicuspid aortic valve after Aortic Valve Replacement: a rare case - Joshi, Dikshya; Bajracharya, Smriti M.; Timala, Rabindra B.; Gautam, Navin C.; Singh, Yogeshwor M.; Thakur, Apurba; Sharma, Jyotindra (Nepalese Heart Journal, 2020)
The occurrence of acute aortic rupture after aortic valve replacement is unusual; but catastrophic. We report a case of a 71-year-old gentleman with a bicuspid aortic valve who developed acute aortic rupture after an elective bioprosthetic aortic valve replacement surgery in which successful repair was carried out with the preservation of the prosthetic valve.